Association of Rho-kinase Gene Polymorphisms with Respiratory Distress Syndrome in Preterm Neonates - Gül Kaya; Ercan Sivasli; Serdar Oztuzcu; Nuriye A. Melekoglu; Esma Ozkara; Unal Sarikabadayi; Abdullah T. Demiryürek (Elsevier, 2017)
Respiratory distress syndrome (RDS) of the newborn is one of the most common causes of morbidity and mortality in preterm infants. Our objective was to determine the association between Rho-kinase (ROCK1 and ROCK2) gene polymorphisms and RDS in preterm neonates. Methods: A total of 193 preterm infants with RDS and 186 preterm infants without respiratory problems were included in this study. Polymorphisms were analyzed in genomic DNA using a BioMark 96.96 dynamic array system. Results: We observed that ROCK1 gene rs2271255 (Lys222Glu) and rs35996865 polymorphisms, and ROCK2 gene rs726843, rs2290156, rs10178332, and rs35768389 (Asp601Val) polymorphisms were associated with RDS. However, no associations were found with rs73963110, rs1515219, rs965665, rs2230774 (Thr431Asn), rs6755196, and rs10929732 polymorphisms. Additionally, 12 haplotypes (6 in ROCK1 and 6 in ROCK2) were found to be markedly associated with RDS. Conclusion: This is the first study to examine the involvement of ROCK gene variation in the risk of incident RDS. The results strongly suggest that ROCK gene polymorphisms may modify individual susceptibility to RDS in the Turkish population.